Properties and Performance of Fishing Hooks - M.D., Varghese; V.C., George; A.G., Gopalakrishna Pillai; K., Radhalakshmi (Fishery Technology, 2025)
The physical and chemical properties of indigenous as well as imported hooks along with comparative fishing performance are studied. The inter relationship between different numbering systems and dimensions are worked out. It was observed that the physical parameters and breaking load were independent of hook shape. The proportion of constituent elements differed in different samples. The hooks with a coating of Nickel and Tin did not register signs of corrosion. The hooking rate of both imported and indigenous hooks was comparable but the latter was fragile and prone to deformation. Cataloguing of the physical parameters and properties of indigenous hooks and their inter relationships will serve as a reference guide for manufacturers to offer appropriate hook sizes for the users.